“PROFIL KONDISI FISIK ATLET DAYUNG PORPOV KOTA CIMAHI 2022” - Amrul Hayat (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2022)
This research is a type of descriptive research with a survey method which aims to find out the profile of the physical condition of Porpov rowing athletes in Cimahi City in 2022. To find out the research "Physical Condition Profile of Porpov Rowing Athletes in Cimahi City 2022" from the aspect of the 1000 Meter Distance Canoe Test, 15 Minute Running Test (Vo2 Max), Local Endurance, Bench Press Strength, Bench Pull Strength. Based on the problem studied, namely regarding data collection on the Physical Condition of Cimahi City Porpov Rowing Athletes 2022", then in this study, the population was 16 Cimahi rowing athletes who took part in Porpov. In performing Power, Endurance, Strength, athletes are required to achieve the perfect, very good and good categories, so ideally Cimahi City rowing athletes are 43.9-50.2. Based on the results of the overall data analysis of the level of ability of Cimahi City rowing athletes, the categories achieved by the average rowing athlete are good and very good, this can be seen from the results of the 1000 M Distance Canoeing ability test, 15 minute running test, Bench Press Strength, Bench Pull strength which shows the perfect category is 0.0.0%, the very good category is 0.10.13%, the good category is 15.6.3%, the fair category is 1.0.0%, the poor category is 0.0.0%, the very category less than 0.0.0%.